Current trends in planar Hall effect sensors: evolution, optimization, and applications - Elzwawy, Amir; Piskin, Hasan; Akdogan, Numan; Volmer, Marius; Reiss, Gunter; Marnitz, Luca; Moskaltsova, Anastasiia (Iop Publishing Ltd, 2021)
The advantages of planar Hall effect (PHE) sensors-their thermal stability, very low detection limits, and high sensitivities-have supported a wide range of advanced applications such as nano-Tesla (nT) magnetometers, current sensing, or low magnetic moment detection in lab-on-a-chip devices. In this review we outline the background and implications of these PHE sensors, starting from fundamental physics through their technological evolution over the past few decades. Key parameters affecting the performance of these sensors, including noise from different sources, thermal stability, and magnetoresistance magnitudes are discussed. The progression of sensor geometries and junctions from disk, cross-to-bridge, ring, and ellipse configuration is also reviewed. The logical sequence of these structures from single magnetoresistive layers to bi-, tri-layers, and spin-valves is also covered. Research contributions to the development of these sensors are highlighted with a focus on microfluidics and flexible sensorics. This review serves as a comprehensive resource for scientists who wish to use PHE for fundamental research or to develop new applications and devices. The conclusions from this report will benefit the development, production, and performance evaluation of PHE-based devices and microfluidics, as well as set the stage for future advances.
Keywords: planar Hall effect; sensors; permalloy; magnetoresistance; thin films; NiFe; IrMn